The quality of compost was improved by low concentrations of fulvic acid owing to its optimization of the exceptional microbial structure. (December 2021) - Li, Fang; Yu, Haiyou; Li, Yue; Wang, Yi; Shen Resource, Jinwen; Hu, Desheng; Feng, Biao; Han, Yanlai
Graphical abstract: Highlights: The composting process was significantly accelerated by 100 mg/kg fulvic acid. Fulvic acid results in compost with high ammonium nitrogen and rate of germination. Eighty percent of the microbial taxa responded to the addition of fulvic acid. Beneficial microbes were enriched by fulvic acid, while pathogens decreased. The co-occurrence network changed as the fermentation proceeded. Abstract: The influence of different concentrations of fulvic acid at 0, 100, 200, and 400 mg/kg was evaluated during the course of composting with straw and mushroom residues as substrates. The optimal concentration of fulvic acid is 100 mg/Kg based on microbial characteristics, chemical parameters, and germination index testing. Nearly 80% of the microbial taxa responded significantly to fulvic acid over the composting period, with a dynamic change of the co-occurrence network from complex to simple and then to complex. Fulvic acid accelerated the progress of composting and reduced the emission of gases at the thermophilic phase. The optimal concentration of fulvic acid enriched the beneficial microorganisms Aeribacillus, Oceanobacillus, and Rhodospirillaceae, and decreased the abundances of pathogenic microorganisms Corynebacterium, Elizabethkingia, and Sarcocystidae . This study indicates a new strategy to optimize the composting process using the biostimulant fulvic acid.